(untitled) (Global Journal of Management and Business Research, 2021)
Business analytics is a highly trendin job role in modern world and demand is creating for quality business analysts day by day. Sri Lanka is developing country which is creating valuable job opportunities in the cooperate business environment. Graduates and undergraduates are seeking demanding job roles such as business analysts and they are willing to acquire the education needs which demanded for those job roles.